2005
DOI: 10.1021/pr050205c
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Myelin Proteins by 2D-Gel Electrophoresis and Multidimensional Liquid Chromatography Coupled to MALDI TOF−TOF Mass Spectrometry

Abstract: The myelin sheath is an electrically insulating layer that consists of lipids and proteins. It plays a key role in the functioning of the nervous system by allowing fast saltatory conduction of nerve pulses. Profiling of the proteins present in myelin is an indispensable prerequisite to better understand the molecular aspects of this dynamic, functionally active membrane. Two types of protein, the myelin basic protein and the proteolipid protein, account for nearly 85% of the protein content in myelin. Identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 47 publications
6
76
0
Order By: Relevance
“…This may be linked to structural changes or remodeling occurring after D 9 -THC exposure in adolescents and is consistent with observations of cytoarchitectural changes occurring with cannabinoid treatment (Tagliaferro et al, 2006) and other reports of altered expression of the structural-related proteins tubulin and actin (Tahir et al, 1992;Wilson et al, 1996). MBP is a major constituent of the myelin sheath that allows fast saltatory conduction of nerve pulses (Vanrobaeys et al, 2005). Previous studies employing microarray techniques have demonstrated downregulated MBP expression immediately after chronic D 9 -THC administration (Kittler et al, 2000;Grigorenko et al, 2002).…”
Section: Protein Expression Profiles In Adolescent Brainsmentioning
confidence: 99%
“…This may be linked to structural changes or remodeling occurring after D 9 -THC exposure in adolescents and is consistent with observations of cytoarchitectural changes occurring with cannabinoid treatment (Tagliaferro et al, 2006) and other reports of altered expression of the structural-related proteins tubulin and actin (Tahir et al, 1992;Wilson et al, 1996). MBP is a major constituent of the myelin sheath that allows fast saltatory conduction of nerve pulses (Vanrobaeys et al, 2005). Previous studies employing microarray techniques have demonstrated downregulated MBP expression immediately after chronic D 9 -THC administration (Kittler et al, 2000;Grigorenko et al, 2002).…”
Section: Protein Expression Profiles In Adolescent Brainsmentioning
confidence: 99%
“…Among the traditional mass spectrometric methods available for identification of proteins separated by 2-D gel, PMF by MALDI-TOF MS [13] and MALDI-TOF/TOF MS [14], and ESI-MS/MS [15] have been used almost exclusively for this application. Due to its inherent simplicity and relatively high sample throughput, MALDI-TOF is commonly used as a screening method for direct analysis of gel-extracted peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its inherent simplicity and relatively high sample throughput, MALDI-TOF is commonly used as a screening method for direct analysis of gel-extracted peptides. Confidence in correct identification of the proteins by this approach can be increased through the inclusion of a tandem TOF (TOF/TOF) mass analysis [14]. For spots that fail to be identified in the initial screening process, an additional analysis using either LC-MALDI-MS/MS, or LC-ESI-MS/MS can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…MAG-related peptides were not detected in these experiments; however, it is unclear if this finding is due to lack of XMMP-28 degradation or difficulty in proteomic detection of this protein (Vanrobaeys et al, 2005).…”
Section: Xmmp-28 Demonstrates Activity Against Myelin Componentsmentioning
confidence: 69%